2007
DOI: 10.1188/07.onf.1211-1217
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Breast Cancer Screening Among Jordanian Nurses

Abstract: Continuing education programs for nurses are urgently needed to improve nurses' knowledge about breast cancer and BSE. Additional studies to examine the impact of other variables on the practice of early-detection methods should be conducted, such as those that determine faculty knowledge and beliefs about early detection, those that assess curriculum content about breast cancer and its early detection, and those that assess other healthcare providers' knowledge and beliefs about early detection. Intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 13 publications
6
37
3
2
Order By: Relevance
“…Reports from similar studies on FHPs in Turkey (10,11,15,18) and other countries (13,14,(19)(20)(21) are consistent with the results of this study. As is already known, FHPs are given theoretical information about BC and screening behaviors as part of their training.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Reports from similar studies on FHPs in Turkey (10,11,15,18) and other countries (13,14,(19)(20)(21) are consistent with the results of this study. As is already known, FHPs are given theoretical information about BC and screening behaviors as part of their training.…”
Section: Discussionsupporting
confidence: 82%
“…As is already known, FHPs are given theoretical information about BC and screening behaviors as part of their training. Prior studies suggested that knowledge leads to improved attitudes and practice due to increased awareness (20,22). However, information is not always sufficient to increase compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Results of other studies support our findings: breast cancer risk factors have been reported as never given birth, low fertility rate, late pregnancy, early menstruation, late menopause, history of breast disease, advanced age, physical inactivity and lack of exercise, fat-rich diet, smoking, alcohol intake, family history of breast cancer, obesit, prolonged use of contraceptives, high socioeconomic status and working women (10,11,13,20,21,23,25). Although the level of information of the nurses regarding breast cancer risk factors vary according to studies, Ahmed et al (20) have reported this level among nurses in Karachi from 7 hospitals as 35% good , 40% moderate , and 25% poor.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies regarding knowledge and practices of nurses on breast cancer prevention from Turkey (11)(12)(13)(17)(18)(19) and abroad (10,(20)(21)(22)(23)(24)(25)(26)(27) have showed significant differences in knowledge and application of BSE, CBE and mammography among nurses. These differences are thought to originate from research methodology, nurses' socio -demographic (age, education level, marital status, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation